(untitled) (Journal Of Educational and Psychological Researches, 2023)
Volunteerism is an element included in many human cultures. It represents a positive cooperative act between individuals and groups. It expresses the social value systems. As a social phenomenon, it develops in societies according to innumerous circumstances and conditions. This study uses a functional approach that assumes that volunteering performs six functions for volunteers. Namely, we assume that volunteering (1) creates a sense of protection (2) meets significant cultural values (3) improves professional status of volunteers, (4) strengthens their social relationships, (5) helps them achieve a better understanding of life, and finally, (6) enhances their outlook and self-esteem. The central aim of the study is to discuss these functions theoretically and then measure them statistically among a sample of students of the American University of Madaba within their social relations of family, friends and colleagues. The study found a set of results, the most important of which are: (1) The above functions range from high to medium, the highest being reinforcement, followed by protection, then occupation, then social dimension, then understanding, and finally values.